STUDI DESKRIPTIF PENGGUNAAN INTERNET OLEH MAHASISWA DI SEKOLAH TINGGI TEOLOGI KRISTUS ALFA OMEGA SEMARANG TAHUN AJARAN 2018-2019 - Andika Andika; Yohanes Tandi; Fianus Tandiongan (JOURNAL of THEOLOGICAL STUDENTS, 2020)
The author found that the students in Kristus Alfa Omega Theological Seminary are not able to use the internet in supporting the learning process. Therefore, the focus of this research is the extent to which students use the internet as a source of learning. The research method used is quantitative descriptive. The results showed that the level of internet is in the range of Lower and Upper Bound values, 80.35-81-26, and is located in the medium category in the table in class intervals. It means the students are still lacking ability to use the internet as a source of learning.